Benefits and risks of suicide disclosure. (February 2019) - Sheehan, Lindsay; Oexle, Nathalie; Armas, Silvia A.; Wan, Hoi Ting; Bushman, Michael; Glover, LaToya; Lewy, Stanley A.
Abstract: Rationale: Individuals who attempt suicide are often subject to stigma and may feel ashamed to talk openly about their experiences with suicide. However, failure to disclose could interfere with care-seeking, increase distress, and limit social support. While research on other concealable stigmatized conditions (e.g. mental illness and HIV) has identified the complexities of disclosure decisions, little is known about disclosure for suicide attempt survivors. Objective: Given the lack of research in this area, this study aimed to explore suicide attempt survivor perspectives on risks and benefits of suicide disclosure. Methods: Academic researchers partnered with a community-based participatory research team to develop and conduct the research. The team conducted group and individual interviews with U.S. suicide attempt survivors ( n  = 40), using thematic analysis to code responses into themes for benefits ( n  = 12) and risks/barriers ( n  = 10) of disclosing. Results: Participants collectively identified how disclosure could benefit them ( n  = 9) through enhanced social support, strengthening of personal relationships, access to treatment, and opportunities for self-reflection. Participants described how disclosure could benefit others ( n  = 3) by reducing stigma, allowing attempt survivors to help peers who are currently struggling with suicidal ideation, and by providing psychoeducation on suicidality. Participants also described ways that disclosure could put them at risk ( n  = 8), in terms of stigma, unsupportive reactions, unwanted treatment, or loss of privacy. Participants were concerned that disclosure could put confidants at risk ( n  = 2) of being overburdened or triggered. Conclusion: While the study methodology did not allow for an exploration of which benefits or risks may be most salient for suicide attempt survivors, this study lays groundwork for future research on disclosure of suicidal thoughts and behaviors. Furthermore, these results can be used by service providers to support suicide attempt survivors in strategic disclosure decisions that maximize benefits and reduce risks. Highlights: Qualitative methods examined perceived benefits and risks of disclosing suicidality. Participants ( n  = 40) were suicide attempt survivors in the U.S. Disclosure poses both benefits and risks to the discloser and the confidant. Disclosures aid care-seeking and recovery, strengthen relationships and fight stigma. Disclosures can result in discomfort, unwanted treatment, and stigmatizing response.